Congenital quadricuspid aortic valve anomaly associated with hypertrophic non-obstructive cardiomyopathy: a case report and review of the literature. Issue 1 (July 1997) - Janssens, U.; Klues, H. G.; Hanrath, P.
Abstract : A case is reported of a 38 year old woman without known cardiac congenital abnormality but a history of well controlled arterial hypertension who was admitted to hospital after successful resuscitation at home following cardiac arrest. There was no evidence of myocardial infarction on 12-lead electrocardiogram but there were signs of left ventricular hypertrophy. Transoesophageal echocardiography revealed a rare quadricuspid aortic valve (QAV) malformation with concomitant mild aortic regurgitation. The left ventricle showed a massive concentric hypertrophy without obstruction. The patient was eventually transferred in a persistent vegetative state to a home care facility. A review of the literature revealed 70 cases of QAV diagnosed by transthoracic or transoesophageal echocardiography (26 cases), at necropsy (25), during surgery (15), and during angiography (4). The present case is the first report of QAV associated with non-obstructive hypertrophic cardiomyopathy.